Need Analysis on English for Computer and Technique - Hafizah Rifiyanti; Dyah Utami Dewi (LPPM STKIP Kusuma Negara, 2022)
Practice is as important as the theory in learning a language. A recommended syllabus is needed to use in the institution according to the need of the learners as well. This esearch aims to analyze the necessities, the lacks and wants of the learners in the English for Computer and Technique course. The research method is descriptive with a qualitative model. The survey research using a series of questionnaires and was distributed to 32 respondents from the informatics study program. In collecting the data, the researcher applied questionnaire for the students as the instrument of the research. The results of the needs analysis concluded that students need English to improve their speaking, listening, reading, and writing. material that per the field of science, namely computer science, becomes more interesting and strongly supports the knowledge being studied. The implementation of this research is to prepare an Semester Learning Plan in accordance to the student’s needs and to develop lecturer competence as well as technology and information progress.